Analisis Model Literasi Keuangan Syariah Bagi Generasi Milenial Di Jabodetabek - Anak Agung Monny Aryadi Djlantik; Saiful Anwar (ITB AAS INDONESIA Surakarta, 2023)
The Millennial Generation is the largest market share in the future for Islamic banking with a total of 74.93 million or 27.94%; therefore, Islamic financial literacy is very important for the millennial generation. This study aimed to examine the influence of Attitude, Behavior, Knowledge, Skill, and Belief on the Millennial Generation choosing Islamic Financial products and institutions in Indonesia. The object of research is the millennial generation in Jabodetabek. Collective data used a questionnaire with a sample selection technique using purposive sampling, while data analysis techniques used the Structural Equation Model (SEM). The research results prove that of the five variables examined in the Millennial Generation, 3 v3 variables have an on the Millennial generation to choose products for Islamic banking institutions, and two variables have no influence on the Millennial generation in deciding to choose Islamic financial institution products.